PPARδ agonist protects against osteoarthritis by activating AKT/mTOR signaling pathway-mediated autophagy - Sun, Guantong; Li, Xiaodong; Liu, Pengcheng; Wang, Yao; Yang, Cheng; Zhang, Shuhong; Wang, Lei; Wang, Xiaoqing (Frontiers in Pharmacology, 2024)
Osteoarthritis (OA) is the most prevalent degenerative joint disease, and PPARs are involved in its pathogenesis; however, the specific mechanisms by which changes in PPARδ impact the OA pathogenesis yet to be discovered. The purpose of this study was to ascertain how PPARδ affects the onset and development of OA. In vitro, we found that PPARδ activation ameliorated apoptosis and extracellular matrix (ECM) degradation in OA chondrocytes stimulated by IL-1β. In addition, PPARδ activation may modulate AKT/mTOR signaling to partially regulate chondrocyte autophagy and apoptosis. In vivo, injection of PPARδ agonist into the articular cavity improved ECM degradation, apoptosis and autophagy in rats OA models generated by destabilization medial meniscus (DMM), eventually delayed degeneration of articular cartilage. Thus, targeting PPARδ for OA treatment may be a possibility.